1996
DOI: 10.1097/00005537-199602000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Middle Ear Oxygen and Carbon Dioxide Tensions on Eustachian Tube Ventilatory Function

Abstract: The objective of this study was to determine the effect of middle ear (ME) gas composition on eustachian tube ventilatory function (ETVF). ETVF was evaluated by using forced-response and inflation-de-flation tests in four alert cynomolgus monkeys during test sessions with different gas compositions. The ME was flushed with one of the four gas mixtures: 1. air; 2. 12% oxygen, 88% nitrogen; 3. 100% oxygen; and 4. 5% carbon dioxide, 21% oxygen, and 74% nitrogen before and during testing. The results documented lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Suggested sensory components of the proposed neural pathways have been identified in the tympanic cavity mucosa and eustachian tube muscle fibers 5‐7,17 . We have previously shown that exposure of the tympanic cavity to a hyperoxic gas mixture reduced middle ear pressure equalization ability when compared with hypercarbic and hypoxic mixtures 8 . The possible role of changes in the systemic oxygen tension on ETVF control has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suggested sensory components of the proposed neural pathways have been identified in the tympanic cavity mucosa and eustachian tube muscle fibers 5‐7,17 . We have previously shown that exposure of the tympanic cavity to a hyperoxic gas mixture reduced middle ear pressure equalization ability when compared with hypercarbic and hypoxic mixtures 8 . The possible role of changes in the systemic oxygen tension on ETVF control has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring system and test protocols have been described previously and have been employed for ETVF evaluation in humans and several mammal species including the cynomolgus monkey 8‐11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that downregulation of the eustachian tube opening function during systemic hyperoxia is possibly caused by a chemoreceptor tissue response. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The supine and head-down positions frequently assumed in diving further contribute to venous congestion and difficulties in ear clearing [6]. Oxygen-enriched breathing gas mixtures often employed in diving and military flying further reduce middle ear ventilation secondary to mucosal oxygen toxicity or downregulation of chemoreceptor-mediated eustachian tube ventilatory function [7][8][9]. These physiological disadvantages, when combined with too rapid a pressure change, in the absence of active attempts to achieve pressure equalization by Valsalva or similar manoeuvres or in the presence of local inflammation and mucosal swelling, will lead to middle ear barotrauma.…”
Section: Otologic Barotraumamentioning
confidence: 99%